The potential of epigenetic methods to provide evidence of torture - Paula Suárez-López (Torture)
Introduction: The last five decades have wit- nessed a transition from brutal forms of physi- cal torture to other physical and psychological methods that do not leave marks on the body. Providing evidence of these types of torture is often a challenge. Finding biological markers of torture would potentially contribute to solve this problem.